Advances in optics manufacture : selected, peer reviewed papers from the Asia Pacific Conference on Optics Manufacture 2012 (APCOM 2012), August 26-28, 2012, Changchun, China - Asia Pacific Conference on Optics Manufacture (2012 : Changchun, China); Fu, Yuegang (Durnten-Zurich, Switzerland ; Enfield, NH : Trans-Tech Publications Ltd.)
Includes bibliographical references and index